Simultaneous Pell equations - Sihabudin, Nurul Amirah; Sapar, Siti Hasana; Mohamad Johari, Mohamad Aidil (AIP Publishing, 2015)
This paper will discuss the solutions on the simultaneous Pell equations x2 − my2 = 1 and y2 − 11z2 = 1 where m is square free. By looking at the pattern of the solutions, some theorems will be developed. The solutions to these simultaneous equations are (x, y, z, m) = (50i − 1, 10, 3, mi) and (50i + 1, 10, 3, mi) for some expressions of mi where i is natural number.